2018
DOI: 10.1111/aji.13027
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus accelerates re‐epithelialization in vaginal epithelial cell line MS74

Abstract: These results may enhance our knowledge of the importance of L. crispatus in the healing of damaged vaginal epithelium and protection against the consequent risk of pathogenic infections, such as human immunodeficiency virus (HIV), and improve our understanding of vaginal epithelial barrier integrity maintenance by this bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…The results reported here are consistent with how L. casei and B. breve affect gastrointestinal cell proliferation but differ from the reported antimigration effect of G. vaginalis on HeLa cells (51) and promigration effect of L. crispatus on MS374 cells (52). The cancerous cervical origin of both HeLa and MS374 cell lines likely compromises these cells as models to study migration or proliferation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results reported here are consistent with how L. casei and B. breve affect gastrointestinal cell proliferation but differ from the reported antimigration effect of G. vaginalis on HeLa cells (51) and promigration effect of L. crispatus on MS374 cells (52). The cancerous cervical origin of both HeLa and MS374 cell lines likely compromises these cells as models to study migration or proliferation.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely, migration of MS374 cells was increased upon exposure to L. crispatus culture supernatants relative to control cell culture medium (52). In another study, lactate and acetate produced by Lactobacillus casei and Bifidobacterium breve inhibited gut epithelial cell proliferation (53).…”
Section: Discussionmentioning
confidence: 99%
“…L. crispatus and L. gasseri are commensal bacteria found in both human GI tract (Walter, 2008) and lower female urogenital tract. Their implication on women's health have been explored in the recent years (Stapleton et al, 2011;Matsuda et al, 2018;Phukan et al, 2018;Takada et al, 2018). Preliminary clinical trials have shown that intro-vaginal probiotic treatment with L. crispatus (intravaginal suppository probiotic Lactin-V; Osel) could significantly lower the reoccurrence rate of urinary tract infections in premenopausal women (Stapleton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary clinical trials have shown that intro-vaginal probiotic treatment with L. crispatus (intravaginal suppository probiotic Lactin-V; Osel) could significantly lower the reoccurrence rate of urinary tract infections in premenopausal women (Stapleton et al, 2011). L. crispatus JCM 7696 has also been shown to accelerate wound healing in vaginal epithelial cell line (Takada et al, 2018). L. gasseri American Type Culture Collection (ATCC) 9857 has been found to significantly inhibit the adhesion of Trichomonas vaginalis to human vaginal ectocervical cells (Phukan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported recently that L . crispatus promotes repair of injured vaginal epithelial cells by promoting the secretion of vascular endothelial growth factor A (VEGF), which may help to reduce subsequent acquisition of urogenital tract infections [44]. L .…”
Section: Discussionmentioning
confidence: 99%